Document-Centric Software Development is it time to evolve in the XML age?. - Bailey, Steve
At the heart of any software program lies data and in the case of Web services and service-oriented solutions this is presented to the underlying software as XML documents. The representation and handling of these documents within the software is a major challenge with traditional development approaches, and often leads to complicated collections of software programs interfering with the clear flow of business information through an application. This article will show that a new approach is essential in order to simplify the complexity of today's software solutions while significantly reducing the cost of inevitable future change.